Correction to: Case-management protocol for bloody diarrhea as a model to reduce the clinical impact of Shiga toxin-producing Escherichia coli infections. Experience from Southern Italy - Daniela Loconsole; Mario Giordano; Nicola Laforgia; Diletta Torres; Luisa Santangelo; Vincenza Carbone; Antonio Parisi; Michele Quarto; Gaia Scavia; Maria Chironna (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Case-management protocol for bloody diarrhea as a model to reduce the clinical impact of Shiga toxin-producing Escherichia coli infections. Experience from Southern Italy - Daniela Loconsole; Mario Giordano; Nicola Laforgia; Diletta Torres; Luisa Santangelo; Vincenza Carbone; Antonio Parisi; Michele Quarto; Gaia Scavia; Maria Chironna (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To describe an operating protocol for bloody diarrhea (BD) in a pediatric population as a rapid response to a public health threat represented by an excess of pediatric HUS cases in the Apulia region (Southern Italy) starting from 2013. The protocol was set up with the goal of correct clinical management of Shiga toxin-producing Escherichia coli (STEC) infections, reductions in subsequent cases of hemolytic uremic syndrome (HUS), and improved short- and long-term disease outcomes. The protocol consisted of rapid hospitalization of children with bloody diarrhea (BD), hematochemical laboratory tests every 12–24 hours, and prompt laboratory diagnosis of STEC. No antibiotics were recommended until diagnosis. Children positive for STEC infections underwent early vigorous volume expansion. In June–December 2018, 438 children with BD were hospitalized, of which 53 (12.1%) had a STEC infection. The most common serogroups were O26 (36.1%), O111 (23.0%), and O157 (14.8%). Thirty-one samples carried the stx2 gene. Four cases evolved into HUS (7.5%), all with favorable outcome despite neurological involvement in two cases. Prompt and accurate laboratory diagnosis of STEC infections is of the utmost importance in patients with BD for correct clinical management. The strict adherence to the protocol could reduce the progression rate of STEC infections to HUS and prevents complications. Enhanced BD surveillance may help reduce cases of pediatric HUS in Southern Italy.